2006
DOI: 10.1126/science.1127233
|View full text |Cite
|
Sign up to set email alerts
|

Synaptic Amplifier of Inflammatory Pain in the Spinal Dorsal Horn

Abstract: Inflammation and trauma lead to enhanced pain sensitivity (hyperalgesia), which is in part due to altered sensory processing in the spinal cord. The synaptic hypothesis of hyperalgesia, which postulates that hyperalgesia is induced by the activity-dependent long-term potentiation (LTP) in the spinal cord, has been challenged, because in previous studies of pain pathways, LTP was experimentally induced by nerve stimulation at high frequencies ( approximately 100 hertz). This does not, however, resemble the real… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
420
5
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 415 publications
(443 citation statements)
references
References 26 publications
17
420
5
1
Order By: Relevance
“…Several lines of evidence indicate that cGMP can exert pronociceptive effects in NK1-R-positive lamina I projection neurons. In particular, previous studies revealed that long-term potentiation of synapses between C-fibers and lamina I projection neurons is NO dependent (Ikeda et al, 2006), and that selective ablation of these neurons considerably attenuated inflammatory and neuropathic pain (Mantyh et al, 1997;Nichols et al, 1999;Khasabov et al, 2002). However, our data indicate that cGMP produced by NO-GC in inhibitory neurons exerts antinociceptive effects that are mediated by CNGA3.…”
Section: Discussioncontrasting
confidence: 54%
“…Several lines of evidence indicate that cGMP can exert pronociceptive effects in NK1-R-positive lamina I projection neurons. In particular, previous studies revealed that long-term potentiation of synapses between C-fibers and lamina I projection neurons is NO dependent (Ikeda et al, 2006), and that selective ablation of these neurons considerably attenuated inflammatory and neuropathic pain (Mantyh et al, 1997;Nichols et al, 1999;Khasabov et al, 2002). However, our data indicate that cGMP produced by NO-GC in inhibitory neurons exerts antinociceptive effects that are mediated by CNGA3.…”
Section: Discussioncontrasting
confidence: 54%
“…LTP at glutamatergic C-fiber synapses onto lamina I projection neurons has been extensively studied as a cellular mechanism accompanying hyperalgesia (18,(46)(47)(48), but relatively little is known about plasticity at dorsal horn inhibitory synapses (49). To our knowledge, the LTP we describe here is the first example of LTP at glycinergic synapses in the mammalian CNS.…”
Section: Discussionmentioning
confidence: 81%
“…However, when these receptors are exposed to μ-opioid receptor agonists, such as remifentanil, this connection can be broken. This causes an increase in the sensitivity of NMDARs to glutamate and glycine, leading to membrane depolarization (Ikeda et al, 2006). The activated NMDARs then allow Ca 2+ to enter into neurons.…”
Section: Discussionmentioning
confidence: 99%